Alcohol consumption and its effect on testicular structure and on sperm count and motility in parent mice and their offspring - Albadri, C.T.; AlAni, Imad Matloub Dally; Hiba, H .M. A. (International Islamic University Malaysia, 2013)
Introduction: The goal of the present study was to examine the effect of alcohol consumption on sperm count and motility and the morphological changes in the seminiferous tubules of parent mice and their offspring. Methods: Animals were divided into two groups, Group 1 (alcohol group) of twelve male and twelve female mice, were given a daily dose of (3 g/kg body weight as 25%, v/v) ethanol by gastric gavage for four and eight weeks. Group 2 (control group) also of twelve male and twelve female mice; received normal access of food and water. After four weeks of treatment, the males and females in each group were allowed to mate, and ethanol treatment continued for up to another four weeks. Twelve male offspring from group 1 and twelve male offspring from group 2 were selected randomly and allowed to become mature. Male parent mice were killed at the 4 th and 8 weeks of treatment, and their male offsprings were killed when they reached maturity age. Results: Physiological examination of the sperm solution showed that there was a significant decrease in sperm count and motility after 4 and 8 weeks of ethanol treatment in parent male mice, but this decrease was not significant in their adult offspring. Furthermore, histological investigations indicated testicular lesions in the parent male mice and their adult male offspring. Conclusion: Alcohol abuse has deleterious effects on the testes structure and on the sperm count and motility of the epididymal spermatozoa of both parent mice and their offspring.